If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -2y + 9y = -16 Combine like terms: 5y + -2y = 3y 3y + 9y = -16 Combine like terms: 3y + 9y = 12y 12y = -16 Solving 12y = -16 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '12'. y = -1.333333333 Simplifying y = -1.333333333
| 18=5x-3x | | 7-3n=-4n+1 | | 3y^2+9y=0 | | 10-8r=-6r-6 | | 4(x+7)=-4 | | 12-5n=h+6 | | 6x+2y=19 | | 11+6k=1+4k | | 8t+3/5=9 | | y=2/3x | | 3x-11=2(y-4) | | -3z-4=2z-24 | | 3+6x=7x+6-1 | | 17=119/w | | 85/7-52/7 | | 200=5/9(f-32) | | 4b=4b | | 15x^2y^2/3x^10y | | 1+m=-11+6m-7m | | 8x-177+x=57 | | t^2+2t-24= | | 15m^2p^2/3m^10p | | 100=5/9(f-39) | | .25(60+16s)=.33(45+12s) | | 1+4a=-5+3a | | 5n-3=92 | | 5+4z-7=4z-2-z | | 3x-2=9-8x | | 576(72)=d | | x^4-7x^2+20=0 | | 5x+8=6x | | 2x+y-2z=-3 |